Solid-state battery and preparation method thereof

By coating single-ion conductor polymers in situ on the surface of sulfide electrolyte particles, the problem of poor electrochemical stability of sulfide electrolyte in secondary batteries is solved, and higher electrochemical stability and cycle life are achieved.

CN119419337AActive Publication Date: 2025-02-11ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411546436.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing sulfide electrolytes have problems such as poor electrochemical stability, sensitivity to water and low oxidation potential in secondary batteries, resulting in safety hazards and cycling failures.

Method used

The single ion conductor polymer is coated as a cladding layer on the surface of the sulfide electrolyte particles. The single ion conductor polymer is formed by in situ polymerization of specific single ion conductor monomers, which isolates the sulfide electrolyte from the air and the positive electrode active substance. Direct contact and maintain high ionic conductivity.

Benefits of technology

It improves the electrochemical stability and high voltage stability of sulfide electrolytes, extends the cycle life of solid-state batteries, and improves the charge and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419337A_ABST
    Figure CN119419337A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state battery and a preparation method thereof, and belongs to the technical field of secondary batteries. The solid-state battery comprises a solid-state electrolyte, the solid-state electrolyte comprises a sulfide electrolyte and a coating layer, the surface of the sulfide electrolyte is coated with the coating layer, and the coating layer is a single-ion conductor polymer. According to the solid-state electrolyte assembled in the solid-state battery, direct contact between sulfide electrolyte and air and between the sulfide electrolyte and a high-voltage positive active material is isolated by using a single-ion conductor polymer, so that oxidative decomposition of the sulfide electrolyte in the charging and discharging process is avoided, and the storage safety and high-voltage stability of the sulfide electrolyte in a secondary battery are improved; meanwhile, the advantage of high ionic conductivity of the sulfide electrolyte can be kept, so that the electrochemical stability and ionic conductivity of the sulfide electrolyte are improved, and the charge-discharge efficiency and the cycle life of the solid-state battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a solid-state battery and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles and large-scale energy storage technologies, the demand for the safety, energy density, cycle life and cost of lithium-ion secondary batteries is also increasing. The energy density of existing organic liquid lithium-ion batteries is close to the theoretical upper limit; at the same time, flammable organic liquid electrolytes also face the risk of leakage and thermal runaway of batteries. All-solid-state batteries use non-flammable solid electrolytes instead of organic liquid electrolytes, which can simplify battery design, improve battery safety performance and energy density, and widen the battery operating temperature range. Solid electrolytes are the core component of all-solid-state batteries. Developing solid electrolytes with high ionic conductivity, high safety and high stability is the key to developing high-performance all-solid-state batteries.

[0003] At present, the three most widely studied solid electrolytes are oxides, sulfides and polymers. Among them, sulfide electrolytes have attracted much attention due to their high ionic conductivity, low Young's modulus, and easy large-scale processing. However, sulfide electrolytes are extremely sensitive to water and release toxic H2S gas instantly when exposed to a water-containing environment, posing a safety hazard. In addition, the oxidation potential of sulfide electrolytes is generally lower than 3V. When sulfide electrolytes are used with a high-voltage positive electrode with an operating voltage higher than 3V, they will undergo oxidative decomposition during the charge and discharge process, causing battery cycle failure.

[0004] Therefore, it is necessary to design a solid-state battery and a preparation method thereof to solve the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides a solid-state battery and a preparation method thereof, which are used to improve the technical problem in the prior art that the sulfide electrolyte itself has poor electrochemical stability and is difficult to be directly applied to secondary batteries.

[0006] To achieve the above-mentioned object and other related objects, the present invention provides a solid-state battery, which includes a solid-state electrolyte, wherein the solid-state electrolyte includes a sulfide electrolyte and a coating layer, wherein the coating layer is coated on the surface of the sulfide electrolyte, and the coating layer is a single-ion conductor polymer; the single-ion conductor monomer polymerized into the coating layer is selected from at least one of the substances of structural formula (1), structural formula (2), structural formula (3), structural formula (4), structural formula (5) and structural formula (6);

[0007]

[0008] In the formula, R is selected from at least one of H, Cl, and CH3.

[0009] In an example of the present invention, the coating layer has a thickness of 1 to 20 nm.

[0010] In an example of the present invention, the thickness of the coating layer is 7-12 nm.

[0011] In an example of the present invention, the particle size of the sulfide electrolyte is 2-4 μm, and the ionic conductivity of the sulfide electrolyte is greater than 3 mS / cm.

[0012] In one example of the present invention, the sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br and Li 5.5 PS 4.5 Cl 1.5 At least one of .

[0013] The present invention also provides a method for preparing the solid-state battery described in any of the above examples, the method comprising providing a positive electrode sheet, a solid electrolyte membrane and a negative electrode sheet; assembling the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet into a battery cell, and encapsulating the battery cell to obtain a solid-state battery;

[0014] The method for preparing the positive electrode sheet and the solid electrolyte in the solid electrolyte membrane comprises:

[0015] Providing sulfide electrolytes and single-ion conductor monomers;

[0016] The sulfide electrolyte is mixed with the single ion conductor monomer, and the single ion conductor monomer is initiated to polymerize in situ on the surface of the sulfide electrolyte to form a coating layer, so as to obtain a solid electrolyte; the coating layer is a single ion conductor polymer;

[0017] Wherein, the single ion conductor monomer is selected from at least one of the substances of structural formula (1), structural formula (2), structural formula (3), structural formula (4), structural formula (5) and structural formula (6);

[0018]

[0019] In the formula, R is selected from at least one of H, Cl, and CH3.

[0020] In one example of the present invention, a sulfide electrolyte and a single ion conductor monomer are provided, including:

[0021] The sulfide electrolyte is dispersed in a first solvent to obtain a first solution; wherein the first solvent is a solvent having a polarity index lower than 2.5; the initiator and the single ion conductor monomer are dispersed in a second solvent to obtain a second solution; wherein the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, ammonium persulfate, 2,4,6-trimethylbenzoyldiphenylphosphine, and benzophenone, and the second solvent is a solvent having a polarity index of 3 to 7.

[0022] In an example of the present invention, the mass ratio of the sulfide electrolyte to the first solvent is (15-45):100; the mass ratio of the single ion conductor monomer, the initiator and the second solvent is (0.3-3):(0.01-0.03):100.

[0023] In one example of the present invention, the sulfide electrolyte is mixed with the single ion conductor monomer, and the single ion conductor monomer is initiated to polymerize in situ on the surface of the sulfide electrolyte to form a coating layer to obtain a solid electrolyte, comprising:

[0024] The first solution and the second solution are mixed to obtain a mixed solution; the single ion conductor monomer in the mixed solution is initiated to polymerize in situ on the surface of the sulfide electrolyte to form a coating layer; wherein the initiation method is light irradiation, heating or microwave radiation; and the first solvent and the second solvent in the mixed solution are removed to obtain a solid electrolyte.

[0025] The present invention provides a solid-state battery, in which the solid electrolyte assembled in the solid-state battery is coated with a single-ion conductor polymer as a coating layer on the outside of the sulfide electrolyte particles. The single-ion conductor polymer coating layer can isolate the sulfide electrolyte from direct contact with air and high-voltage positive electrode active materials, avoid oxidative decomposition of the sulfide electrolyte during charging and discharging, and improve the storage safety and high-voltage stability of the sulfide electrolyte in the secondary battery; at the same time, it can also maintain the advantage of high ionic conductivity of the sulfide electrolyte, thereby improving the electrochemical stability and ionic conductivity of the sulfide electrolyte, thereby improving the charging and discharging efficiency and cycle life of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0027] Figure 1 Schematic diagram of a process for preparing a solid electrolyte in one embodiment of the present invention;

[0028] Figure 2 This is a flow chart of step S1 in one embodiment of the present invention;

[0029] Figure 3 FIG. 1 is a flow chart of step S2 in an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the present invention, it should be noted that the terms “first” and “second” are only used for description and distinction purposes and cannot be understood as indicating or implying relative importance.

[0032] Sulfide electrolytes have excellent application prospects as solid electrolytes for secondary batteries due to their high ionic conductivity, low Young's modulus, and easy large-scale processing. However, the fragile structural stability of sulfide electrolytes limits their application in secondary batteries, such as easy hydrolysis to produce H2S gas and oxidative decomposition when in contact with positive electrode active substances during charging and discharging. The inventors have found that in order to improve the defect of unstable chemical properties of sulfide electrolytes, the prior art usually coats inorganic materials or organic polymers on the surface of sulfide electrolytes as a coating layer. Although the coating layer of the above materials can isolate the sulfide electrolyte from direct contact with air and positive electrode active substances, and improve the stability of the sulfide electrolyte in secondary batteries, inorganic materials or organic polymers usually do not have ionic conductivity. Using inorganic materials or organic polymers as coating layers greatly attenuates the ionic conductivity of the sulfide electrolyte, affecting the cycle performance of the secondary battery.

[0033] Based on this, the present invention provides a solid-state battery, in which a solid electrolyte assembled in the solid-state battery in situ coats a single-ion conductor polymer on the surface of sulfide electrolyte particles, and the coating layer composed of the single-ion conductor polymer can effectively block moisture in the air from entering the surface of the sulfide electrolyte, thereby avoiding the decrease in conductivity and the release of toxic gases caused by the hydrolysis of the sulfide electrolyte; and can also ensure the smooth transmission of lithium ions between the sulfide electrolyte and the positive electrode active material while isolating the sulfide electrolyte from direct contact with the positive electrode active material, thereby improving the chemical stability of the sulfide electrolyte during the charge and discharge process, and maintaining the high ionic conductivity characteristics of the sulfide electrolyte, thereby improving the charge and discharge efficiency and cycle life of the solid-state battery.

[0034] The above-mentioned solid-state battery is a solid-state lithium-ion secondary battery, which includes a positive electrode plate, a negative electrode plate and a solid electrolyte membrane. The solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate to isolate the positive electrode plate and the negative electrode plate, and serves as a lithium ion conductor between the positive electrode plate and the negative electrode plate.

[0035] The positive electrode sheet and the solid electrolyte membrane, or the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet have a solid electrolyte, the solid electrolyte includes a sulfide electrolyte and a coating layer, the coating layer is coated on the surface of the sulfide electrolyte, the coating layer is a single ion conductor polymer, the single ion conductor polymer has lithium ion conductivity, and can allow lithium ions to migrate and transport in the coating layer. The single ion conductor polymer in the coating layer is coated on the surface of the sulfide electrolyte by in-situ polymerization of a single ion conductor monomer, and the single ion conductor monomer contains a C=C double bond, a polar C=O / S=O bond and a Li + The C=C double bond in the single-ion conductor monomer can produce a free radical polymerization chain reaction under initiation, and the formed long-chain single-ion conductor polymer is tightly wrapped on the surface of the sulfide electrolyte particles. The Li + Ion migration can be carried out under the molecular force between the polar C=O / S=O bonds, realizing lithium ion transmission between the sulfide electrolyte and external substances, such as realizing lithium ion transmission between the sulfide electrolyte and the positive electrode active material, the negative electrode active material and other electrolytes. Compared with inorganic coating layers or ordinary polymer coating layers, the coating layer composed of single-ion conductor polymers can not only isolate the sulfide electrolyte from direct contact with external substances, protect the sulfide electrolyte from oxidation and decomposition during storage and use, but also realize rapid ion transmission between the sulfide electrolyte and external substances, maintaining the high ionic conductivity characteristics of the sulfide electrolyte.

[0036] The single ion conductor monomer is selected from at least one of the substances of formula (1), formula (2), formula (3), formula (4), formula (5) and formula (6). Formula (1), formula (2), formula (3), formula (4), formula (5) and formula (6) are as follows:

[0037]

[0038] In the formula, R is selected from at least one of H, Cl, and CH3.

[0039] In some embodiments, the particle size of the sulfide electrolyte is 2-4 μm, and the ionic conductivity of the sulfide electrolyte is greater than 3 mS / cm.

[0040] In some embodiments, the sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br and Li 5.5 PS 4.5 Cl 1.5 At least one of the above. That is, the sulfide electrolyte can be any one of the above-mentioned types, for example, Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br or Li 5.5 PS 4.5 Cl 1.5 Optionally, the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The sulfide electrolyte may also be any combination of the above-mentioned types, for example, Li3PS4 and Li7P3S 11 The composition of Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 The composition of Li 10 GeP2S 12 and Li 5.5 PS 4.5 Cl 1.5 The composition of Li 10 SnP2S 12 and Li 5.5 PS 4.5 Cl 1.5 The composition of Li6PS5Br and Li 5.5 PS 4.5 Cl 1.5 The composition of Li 10 SnP2S 12 , Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 It should be noted that when the sulfide electrolyte is a composition, there is no restriction on the ratio between the components in the composition, and they can be mixed in any ratio.

[0041] In some embodiments, the thickness of the coating layer is 1 to 20 nm, for example, the thickness of the coating layer may be 1 nm, 3 nm, 5 nm, 7 nm, 9 nm, 10 nm, 12 nm, 15 nm, 18 nm or 20 nm. Optionally, the thickness of the coating layer is 7 to 12 nm, for example, the thickness of the coating layer may be 7 nm, 8 nm, 9 nm, 10 nm, 11 nm or 12 nm. The thickness of the coating layer is within the above range, which can take into account the optimization of the coating effect and the conductive performance of the solid electrolyte. If the coating layer is too thin, it will lead to uneven or incomplete coating of the sulfide electrolyte particles, which may easily expose part of the surface of the sulfide electrolyte to the air or directly contact with the positive electrode active material, thereby affecting the chemical stability of the solid electrolyte in the battery; if the coating layer is too thick, it will cause the conduction of lithium ions between the sulfide electrolyte particles to be blocked, affecting the ionic conductivity of the solid electrolyte.

[0042] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer coated on at least one side of the positive current collector, and the positive active material layer includes a positive electrode material, a positive electrode binder, a positive electrode conductor and a solid electrolyte. The mass ratio of the positive electrode active material, the solid electrolyte, the positive electrode binder and the positive electrode conductor can be (50-75): (20-50): (0-3): (1-3). Among them, the positive electrode material is selected from one or more combinations of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium-rich manganese-based oxide (LRMO) and lithium-containing phosphate. The positive electrode binder is selected from one or more combinations of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, nitrile rubber, hydrogenated nitrile rubber, and styrene-butadiene rubber. The positive electrode conductive agent is, for example, one or a combination of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc. In one example, the positive electrode conductive agent includes carbon black and carbon nanofibers, and the mass ratio of carbon black to carbon nanofibers is 1:(0.2-1.5).

[0043] In some embodiments, the negative electrode plate can be a metal lithium plate, a metal indium plate, or a lithium-containing alloy plate (such as a lithium-tin-indium alloy plate, a lithium-silicon alloy plate, a lithium-tin alloy plate, or a lithium-aluminum alloy plate). For example, in one example, the negative electrode plate is selected from a metal lithium plate.

[0044] In other embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode material, a solid electrolyte, a negative electrode binder, and a negative electrode conductive agent. The mass ratio of the negative electrode active material, the solid electrolyte, the negative electrode binder, and the negative electrode conductive agent can be (50-75): (20-50): (0-3): (1-3). Among them, the negative electrode active material is selected from one or more of tin, artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), natural graphite (block graphite, flake graphite, earthy graphite, etc.), soft carbon, hard carbon, pure silicon (crystalline silicon, amorphous silicon or organic silicon), silicon oxide, silicon carbon compound, nano metal oxide (Fe2O3, CuO, SnO2, Mn3O4 nanoparticles). The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers, or a combination of two or more of them mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), or a combination of several of them mixed in any proportion.

[0045] On the other hand, the present invention also provides a method for preparing a solid-state battery, which comprises: providing a positive electrode sheet, a solid electrolyte membrane and a negative electrode sheet; assembling the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet into a battery cell, and encapsulating the battery cell to obtain a solid-state battery.

[0046] It should be noted that the positive electrode sheet, the negative electrode sheet, the solid electrolyte membrane and the secondary battery assembly process in the secondary battery can be prepared by conventional methods in the art.

[0047] In some embodiments, the positive electrode sheet preparation process is as follows: the positive electrode material, positive electrode binder, positive electrode conductor and solid electrolyte are mixed in a mass ratio of (50-75): (20-50): (0-3): (1-3), and a solvent N-methylpyrrolidone (NMP) is added to adjust the slurry solid content to 55%, and then the mixture is fully stirred and mixed under vacuum to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated on the positive electrode current collector aluminum foil, and then the positive electrode current collector aluminum foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet. Among them, the positive electrode material is, for example, selected from one or more combinations of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium-rich manganese-based oxide (LRMO) and lithium-containing phosphate. The positive electrode binder is selected from one or more combinations of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, nitrile rubber, hydrogenated nitrile rubber, styrene butadiene rubber. The positive electrode conductive agent is selected from one or more combinations of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc.

[0048] In some embodiments, the negative electrode sheet preparation process is as follows: after mixing the negative electrode material, solid electrolyte, negative electrode binder, and negative electrode conductive agent in a mass ratio of (50-75): (20-50): (0-3): (1-3), deionized water is added to adjust the solid content of the slurry to 55%, and then the negative electrode slurry is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on an 8μm negative electrode current collector copper foil; after drying at room temperature, it is transferred to an oven for drying, and then cold pressed, cut, and other processes are performed to obtain a negative electrode sheet. Among them, the negative electrode active material is selected from one or more of tin, artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), natural graphite (block graphite, flake graphite, earthy graphite, etc.), soft carbon, hard carbon, pure silicon (crystalline silicon, amorphous silicon or organic silicon), silicon oxide compounds, silicon carbon compounds, and nano metal oxides (Fe2O3, CuO, SnO2, Mn3O4 nanoparticles). The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers, or a combination of two or more of them mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), and styrene-butadiene rubber (SBR), or a combination of several of them mixed in any proportion.

[0049] In other embodiments, a metal lithium sheet, a metal indium sheet, or a lithium-containing alloy sheet (such as a lithium-tin-indium alloy sheet, a lithium-silicon alloy sheet, a lithium-tin alloy sheet, or a lithium-aluminum alloy sheet) is used as the negative electrode sheet.

[0050] In some embodiments, the preparation process of the solid electrolyte membrane is as follows: after mixing the solid electrolyte and the binder in a mass ratio of (90-99.5): (0.5-10), adding them to a low polarity solvent, stirring and mixing them thoroughly to obtain a slurry; after coating the slurry on a substrate, heating and drying the solvent in the coating layer, and peeling the coating layer from the substrate to obtain a solid electrolyte membrane. The binder is selected from any one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and ethylene-tetrafluoroethylene copolymer, or a combination of several mixed in any proportion.

[0051] The following is an example description of the assembly method of the secondary battery: integrating the positive electrode sheet on one side of the solid electrolyte membrane, for example, placing the solid electrolyte membrane on the positive electrode active material layer of the positive electrode sheet, and pressing the solid electrolyte membrane and the positive electrode sheet into one at a pressure of 300 MPa; and then integrating the negative electrode sheet on the other side of the solid electrolyte membrane, for example, placing the negative electrode sheet on the other side of the solid electrolyte membrane, so that the negative electrode active material layer of the negative electrode sheet is in contact with the solid electrolyte membrane, and pressing the negative electrode sheet, the solid electrolyte membrane and the positive electrode sheet into one at a pressure of 300 MPa; after sealing and packaging the pressed battery cell under vacuum or inert atmosphere, a solid-state lithium-ion battery can be obtained.

[0052] like Figure 1 As shown, the method for preparing the solid electrolyte in the above solid-state battery comprises the following steps:

[0053] S1. providing a sulfide electrolyte and a single ion conductor monomer;

[0054] S2, mixing the sulfide electrolyte with the single ion conductor monomer, and initiating in-situ polymerization of the single ion conductor monomer on the surface of the sulfide electrolyte to form a coating layer, so as to obtain a solid electrolyte;

[0055] The coating layer is a single ion conductor polymer formed by in-situ polymerization of a single ion conductor monomer on the surface of the sulfide electrolyte particles. The single ion conductor monomer used in step S1 is selected from at least one of the substances of structural formula (1), structural formula (2), structural formula (3), structural formula (4), structural formula (5) and structural formula (6). Structural formula (1), structural formula (2), structural formula (3), structural formula (4), structural formula (5) and structural formula (6) are as follows:

[0056]

[0057] In the formula, R is selected from at least one of H, Cl, and CH3.

[0058] like Figure 2 As shown, in some embodiments, step S1 includes the following steps:

[0059] S11, dispersing a sulfide electrolyte into a first solvent to obtain a first solution;

[0060] S12, dispersing the initiator and the single ion conductor monomer into a second solvent to obtain a second solution.

[0061] In some embodiments, in step S11, the sulfide electrolyte and the first solvent are uniformly mixed in a mass ratio of (15-45):100 to obtain a first solution;

[0062] Among them, the sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br and Li 5.5 PS 4.5 Cl 1.5 One or more; Optionally, the sulfide electrolyte is selected from Li 5.5 PS 4.5 Cl 1.5 The particle size of the sulfide electrolyte selected in step S11 is 2-4 μm, and the ion conductivity is greater than 3 mS / cm.

[0063] The first solvent is a low-polarity solvent having a polarity index lower than 2.5, for example, the first solvent is selected from at least one of toluene, xylene, n-pentane, hexane and cyclohexane. Optionally, the first solvent is xylene.

[0064] In some embodiments, in step S12, the single ion conductor monomer, the initiator and the second solvent are uniformly mixed in a mass ratio of (0.3-3):(0.01-0.03):100 to obtain a second solution.

[0065] The initiator is used to promote the polymerization of the single ion conductor monomer under initiation conditions, and the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, ammonium persulfate, 2,4,6-trimethylbenzoyldiphenylphosphine and benzophenone. Optionally, the initiator is azobisisobutyronitrile.

[0066] The second solvent is a medium polar solvent with a polarity index of 3 to 7, for example, the second solvent is at least one of ethyl acetate, butyl butyrate, benzyl acetate, acetonitrile and dichloromethane. Optionally, the second solvent is butyl butyrate.

[0067] In some embodiments, the dispersion treatment in step S11 and step S12 may be one or a combination of ultrasound, stirring and ball milling.

[0068] like Figure 3 As shown, in some embodiments, step S2 includes the following steps:

[0069] S31, mixing the first solution and the second solution to obtain a mixed solution;

[0070] S32, initiating the single ion conductor monomer in the mixed solution to polymerize in situ on the surface of the sulfide electrolyte to form a coating layer; wherein the initiation method is light irradiation, heating or microwave radiation;

[0071] S33, removing the first solvent and the second solvent from the mixed solution to obtain a solid electrolyte.

[0072] In step S31, the thickness of the coating layer formed on the surface of the sulfide electrolyte can be controlled by adjusting the mixing ratio of the first solution and the second solution. For example, in some embodiments, the first solution and the second solution are mixed in a mass ratio of (50-100):100 to control the thickness of the coating layer formed on the surface of the sulfide electrolyte to be 1-20 nm.

[0073] In step S31, after the first solution and the second solution are mixed, they are stirred at room temperature for 30 to 60 minutes to make the first solution and the second solution uniformly mixed.

[0074] In step S32, an initiation method is used to cause the single ion conductor monomers in the mixed solution to polymerize in situ on the surface of the sulfide electrolyte under the action of an initiator to form a coating layer. The initiation method can be light irradiation, heating or microwave radiation. For example, in some embodiments, the mixed solution is placed under 100W ultraviolet light for 30 minutes to 2 hours to cause the single ion conductor monomers in the mixed solution to polymerize in situ on the surface of the sulfide electrolyte; in other embodiments, the mixed solution is placed under microwave radiation for 2 to 4 hours to cause the single ion conductor monomers in the mixed solution to polymerize in situ on the surface of the sulfide electrolyte; in some other embodiments, the mixed solution is placed under heating at 60°C for 30 minutes to 2 hours to cause the single ion conductor monomers in the mixed solution to polymerize in situ on the surface of the sulfide electrolyte.

[0075] In some embodiments, in step S33, the mixed solution is centrifuged or filtered, and then the mixed solution is placed in a vacuum dryer at a temperature of 45°C to 60°C for 2 to 8 hours to remove the first solvent and the second solvent in the mixed solution, thereby obtaining a solid electrolyte.

[0076] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.

[0077] Example 1

[0078] This embodiment provides a solid electrolyte, which includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles, and the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The preparation method of the solid electrolyte is as follows:

[0079] S1. In a glove box filled with argon atmosphere, weigh 2.5 g of sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 and 10g of the first solvent xylene are placed in a 50ml glass sample bottle, mixed and stirred at room temperature for 60 minutes to obtain a first solution; 0.01g of the single ion conductor monomer of the structural formula (1), 0.001g of the initiator azobisisobutyronitrile, and 10g of the second solvent butyl butyrate are weighed in another 50ml glass sample bottle, stirred at 45°C for 60 minutes to obtain a second solution, wherein the R group in the structural formula (1) is H;

[0080] S2. Mix the first solution and the second solution, and stir them at room temperature for 60 minutes to obtain a uniform mixed solution; then heat and stir the mixed solution at 60°C for 30 minutes, so that the single ion conductor monomer in the mixed solution is in situ polymerized on the surface of the sulfide electrolyte under the catalysis of the initiator to form a single ion conductor polymer coating layer; after centrifuging the mixed solution, vacuum dry it at 45°C to 60°C for 2 to 8 hours to remove the first solvent and the second solvent in the mixed solution, thereby obtaining a solid electrolyte.

[0081] Example 2

[0082] In this embodiment, a solid electrolyte of the same system as that of embodiment 1 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 1 is that in step S1, 0.03 g of the single ion conductor monomer of structural formula (1), 0.001 g of initiator azobisisobutyronitrile, and 10 g of the second solvent butyl butyrate are weighed and mixed in another 50 ml glass sample bottle.

[0083] Example 3

[0084] In this embodiment, a solid electrolyte of the same system as that of embodiment 1 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 1 is that in step S1, 0.06 g of the single ion conductor monomer of structural formula (1), 0.004 g of initiator azobisisobutyronitrile, and 10 g of the second solvent butyl butyrate are weighed and mixed in another 50 ml glass sample bottle.

[0085] Example 4

[0086] In this embodiment, a solid electrolyte of the same system as that of embodiment 1 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 1 is that in step S1, 0.1 g of the single ion conductor monomer of structural formula (1), 0.006 g of initiator azobisisobutyronitrile, and 10 g of the second solvent butyl butyrate are weighed and mixed in another 50 ml glass sample bottle.

[0087] Example 5

[0088] In this embodiment, a solid electrolyte of the same system as that of embodiment 1 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 1 is that in step S1, 0.3 g of the single ion conductor monomer of structural formula (1), 0.02 g of initiator azobisisobutyronitrile, and 10 g of the second solvent butyl butyrate are weighed and mixed in another 50 ml glass sample bottle.

[0089] Example 6

[0090] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 3 is that in step S1, 4.5 g of sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 and 10 g of the first solvent xylene were placed in a 50 ml glass sample bottle and mixed.

[0091] Example 7

[0092] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 3 is that the initiator used in step S2 is dibenzoyl peroxide, and the mixed solution is irradiated under ultraviolet light with a power of 100 W for 30 minutes to induce the single ion conductor monomer in the mixed solution to form a coating layer on the surface of the sulfide electrolyte.

[0093] Example 8

[0094] This embodiment prepares a solid electrolyte of the same system as that of embodiment 3, the solid electrolyte comprising a sulfide electrolyte and a coating layer coated on the outside of the sulfide electrolyte particles, the sulfide electrolyte is Li6PS5Cl, and the coating layer is a single ion conductor polymer formed by polymerization of a single ion conductor monomer of structural formula (1). The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte is Li6PS5Cl.

[0095] Example 9

[0096] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (2). The difference between this embodiment and embodiment 3 is that in step S1, a single ion conductor monomer of structural formula (2) is selected, and the R group in structural formula (2) is H.

[0097] Example 10

[0098] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (3). The difference between this embodiment and embodiment 3 is that in step S1, a single ion conductor monomer of structural formula (3) is selected, and the R group in structural formula (3) is H.

[0099] Embodiment 11

[0100] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (4). The difference between this embodiment and embodiment 3 is that in step S1, a single ion conductor monomer of structural formula (4) is selected, and the R group in structural formula (4) is H.

[0101] Example 12

[0102] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (5). The difference between this embodiment and embodiment 3 is that in step S1, a single ion conductor monomer of structural formula (5) is selected, and the R group in structural formula (5) is H.

[0103] Example 13

[0104] In this embodiment, a solid electrolyte of the same system as that of embodiment 3 is prepared. The solid electrolyte includes a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (6). The difference between this embodiment and embodiment 3 is that in step S1, a single ion conductor monomer of structural formula (6) is selected, and the R group in structural formula (6) is H.

[0105] Comparative Example 1

[0106] This comparative example provides a non-coated solid electrolyte Li 5.5 PS 4.5 Cl 1.5 .

[0107] Comparative Example 2

[0108] In this comparative example, a solid electrolyte of the same system as that of Example 3 is prepared. The solid electrolyte comprises a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The coating layer is a single ion conductor polymer formed by polymerizing a single ion conductor monomer of structural formula (1). The difference between this comparative example and Example 3 is that in step S1, 0.8 g of the single ion conductor monomer of structural formula (1), 0.02 g of initiator azobisisobutyronitrile, and 10 g of the second solvent butyl butyrate are weighed and mixed in another 50 ml glass sample bottle.

[0109] Comparative Example 3

[0110] Comparative Example 3 provides a solid electrolyte coated with a common polymer, the solid electrolyte comprising a sulfide electrolyte and a coating layer coated outside the sulfide electrolyte particles, the sulfide electrolyte is Li6PS5Cl, and the coating layer is a polymer of methyl methacrylate. The preparation method of the solid electrolyte is as follows:

[0111] S1. In a glove box filled with argon atmosphere, weigh 2.5 g of sulfide electrolyte Li6PS5Cl and 10 g of the first solvent cyclohexane into a 50 ml glass sample bottle, mix and stir at room temperature for 60 minutes to obtain a first solution; weigh 0.06 g of methyl methacrylate, 0.004 g of initiator azobisisoheptanenitrile, and 10 g of the second solvent benzyl acetate into another 50 ml glass sample bottle, stir at 45°C for 60 minutes to obtain a second solution;

[0112] S2. Mix the first solution and the second solution, and stir them at room temperature for 60 minutes to obtain a uniform mixed solution; then heat the mixed solution at 60°C and stir for 30 minutes, so that the methyl methacrylate monomer in the mixed solution is in situ polymerized on the surface of the sulfide electrolyte under the catalysis of the initiator to form a polymer coating layer; after centrifuging the mixed solution, vacuum dry it at 45°C to 60°C for 2 to 8 hours to remove the first solvent and the second solvent in the mixed solution, thereby obtaining a solid electrolyte.

[0113] To further verify the efficacy of the present invention, the ionic conductivity and conductive stability of the solid electrolytes prepared in Examples 1 to 13 and Comparative Examples 1 to 3 when stored in the air were first tested to verify that the solid electrolytes improved the structural stability of the sulfide electrolytes stored in the air while maintaining the high ionic conductivity of the sulfide electrolytes. The test results are shown in Table 1.

[0114] Ionic conductivity test: Weigh 0.1 g of the solid electrolyte powder prepared in the embodiment and the comparative example, and press the solid electrolyte powder into an electrolyte ceramic sheet at a pressure of 200 MPa; attach stainless steel current collectors on both sides of the electrolyte ceramic sheet, and press and assemble it into a mold battery under a pressure of 200 MPa; use an electrochemical workstation to test the AC impedance spectrum of the mold battery to obtain the impedance of the electrolyte ceramic sheet, and then calculate the ionic conductivity σ of the solid electrolyte at room temperature based on the formula σ=L / RS; wherein L is the thickness of the electrolyte ceramic sheet (in cm), R is the impedance of the electrolyte ceramic sheet (in Ω), and S is the contact area (in cm 2 ).

[0115] Conductive stability test stored in air: weigh 0.2g of the solid electrolyte powder prepared in the embodiment and the comparative example, press the solid electrolyte powder into an electrolyte ceramic sheet at a pressure of 200MPa, and perform an impedance test on the electrolyte ceramic sheet using an electrochemical workstation to obtain the initial ionic conductivity of the solid electrolyte; place the electrolyte ceramic sheet in a 5mL open glass bottle, and then place the glass bottle in a reaction box with a specific humid air flow, the relative humidity of the humid air is 10%, the gas flow rate is 100ml / min, and after standing at room temperature for 12h, perform an impedance test on the electrolyte ceramic sheet to obtain the ionic conductivity of the solid electrolyte after exposure to humid air; and compare the ionic conductivity of the solid electrolyte before and after exposure to obtain the retention rate of the ionic conductivity of the solid electrolyte.

[0116] Then, the solid electrolytes prepared in Examples 1 to 13 and Comparative Examples 1 to 3 were assembled into solid-state batteries, and the electrochemical stability of the solid electrolytes prepared in Examples 1 to 13 and Comparative Examples 1 to 3 in the solid-state batteries was tested. The test results are shown in Table 2.

[0117] The solid-state battery preparation process is as follows: weigh 0.2g of solid electrolyte powder and place it in a solid-state battery mold, press it at a pressure of 200Mpa for 5 minutes to obtain a solid electrolyte sheet. Disperse the positive electrode material, solid electrolyte, positive electrode adhesive nitrile rubber, positive electrode conductive agent SuperP and CNT in xylene according to a mass ratio of 70:25:3:1:1, and adjust the amount of xylene added to control the solid content of the slurry to about 55%; use a doctor blade method to apply the slurry on the positive electrode current collector aluminum foil, place the coated positive electrode sheet at 100°C for 2 hours, and then roll and compact it at 60°C at a pressure of 95MPa to obtain a positive electrode sheet. The solid electrolyte sheet is integrated on the side of the positive electrode plate where the positive electrode active material layer is set, and is pressed together at a pressure of 100 MPa; a lithium indium alloy sheet is used as a negative electrode plate, and the negative electrode plate is integrated on the side of the solid electrolyte sheet away from the positive electrode plate, and is pressed together at a pressure of 100 MPa to obtain a battery cell; the battery cell is heat-packaged, and then subjected to processes such as standing, hot and cold pressing, formation, clamping, and capacity division to obtain a solid-state battery.

[0118] The first coulombic efficiency test of solid-state batteries: At room temperature of 25°C, in the test voltage range of 2.5V (discharge cut-off voltage) to 4.2V (charge cut-off voltage), with a charge and discharge current rate of 0.1C / 0.1C, the solid-state battery was subjected to the first week of charge and discharge test, and the first charge capacity and first discharge capacity of the battery were recorded. The first discharge capacity in grams was divided by the mass of the negative electrode to obtain the first discharge capacity in grams, and thus the first coulombic efficiency.

[0119] Cycling performance test of solid-state batteries: At room temperature of 25°C, in the test voltage range of 2.5V (discharge cut-off voltage) to 4.2V (charge cut-off voltage), the solid-state batteries were charged and discharged for 3 weeks at charge and discharge current rates of 0.2C / 0.2C, 0.5C / 0.5C, 1C / 1C, and 2C / 2C respectively; then, the solid-state batteries were charged and discharged at a charge and discharge current rate of 0.5C / 0.5C. When the discharge capacity of the solid-state battery reached 80% of the first discharge capacity at the 0.5C rate, the test was stopped and the number of cycles at room temperature was recorded.

[0120] Table 1: Test results of ionic conductivity and air storage stability of solid electrolytes prepared in Examples 1 to 13 and Comparative Examples 1 to 3

[0121]

[0122] Table 2: Battery performance test results of solid electrolytes prepared in Examples 1 to 13 and Comparative Examples 1 to 3

[0123]

[0124]

[0125] By comparing the test results of Examples 1 to 13 and Comparative Example 1, it can be seen that the sulfide electrolyte with a surface coated with a single-ion conductor polymer has both good electrochemical stability and high lithium ion conductivity, and the solid-state battery assembled therefrom also has better cycle performance.

[0126] Comparing the test results of Example 3 and Comparative Example 1, it can be seen that compared with the sulfide electrolyte without a coating layer, the ionic conductivity of the sulfide electrolyte coated with the single-ion conductor polymer is only slightly reduced, and the ionic conductivity drop is significantly reduced after exposure to humid air, and the ionic conductivity retention rate in humid air is significantly improved, which proves that the single-ion conductor polymer coating layer can effectively block the corrosion of water to the sulfide electrolyte and improve the air stability and use safety of the sulfide electrolyte. In addition, the first coulomb efficiency and cycle capacity retention rate of the solid-state battery equipped with the coated sulfide electrolyte are also significantly improved, proving that the solid electrolyte in the embodiment also has excellent electrochemical stability when used in the battery.

[0127] Comparing the test results of Example 8 and Comparative Example 3, it can be seen that compared with the sulfide electrolyte coated with ordinary polymer, the ionic conductivity of the sulfide electrolyte coated with single ion conductor polymer is significantly improved, and the first coulomb efficiency and cycle capacity retention rate of the solid-state battery equipped with single ion conductor polymer coated sulfide electrolyte are also improved. This is because the ion conductor polymer coating layer can not only block the direct contact between the sulfide electrolyte particles and the positive electrode active material particles, but also can quickly conduct ions between the sulfide electrolyte particles and between the sulfide electrolyte particles and the positive electrode active material particles, thereby reducing the charge transfer impedance of the interface.

[0128] Further, by comparing the test results of Examples 1 to 6 and Comparative Example 2, it can be seen that the coating thickness is optimized within an appropriate range.

[0129] Comparing the test results of Examples 1 to 6 and Comparative Example 2, it can be seen that as the thickness of the coating layer increases, the storage stability of the solid electrolyte in the air is significantly improved, but the corresponding sulfide electrolyte content and ionic conductivity loss also increase. For example, when the coating layer thickness in Comparative Example 3 is greater than 20nm, the ionic conductivity of the solid electrolyte is only 23% of that of the uncoated sulfide electrolyte. Therefore, it is necessary to control the coating layer thickness to be below 20nm to achieve a balance between air stability and high ionic conductivity.

[0130] In summary, the present invention provides a solid electrolyte, a secondary battery, and a method for preparing a solid electrolyte, wherein the solid electrolyte is coated with a single ion conductor polymer as a coating layer on the outside of sulfide electrolyte particles. The single ion conductor polymer coating layer can isolate the sulfide electrolyte from direct contact with air and high-voltage positive electrode active materials, avoid oxidative decomposition of the sulfide electrolyte during charging and discharging, and improve the storage safety and high-voltage stability of the sulfide electrolyte in the secondary battery; at the same time, it can also maintain the advantage of high ionic conductivity of the sulfide electrolyte, thereby improving the electrochemical stability and ionic conductivity of the sulfide electrolyte.

[0131] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A solid-state battery, characterized in that: The invention comprises a solid electrolyte, wherein the solid electrolyte comprises a sulfide electrolyte and a coating layer, wherein the coating layer is coated on the surface of the sulfide electrolyte, and the coating layer is a single ion conductor polymer; the single ion conductor monomer polymerized into the coating layer is selected from at least one of the substances of structural formula (1), structural formula (2), structural formula (3), structural formula (4), structural formula (5) and structural formula (6); In the formula, R is selected from at least one of H, Cl, and CH3.

2. The solid-state battery according to claim 1, characterized in that: The coating layer has a thickness of 1 to 20 nm.

3. The solid-state battery according to claim 2, characterized in that: The coating layer has a thickness of 7 to 12 nm.

4. The solid-state battery according to claim 1, characterized in that: The particle size of the sulfide electrolyte is 2-4 μm, and the ion conductivity of the sulfide electrolyte is greater than 3 mS / cm.

5. The solid-state battery according to claim 1, characterized in that: The sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br and Li 5.5 PS 4.5 Cl 1.5 At least one of .

6. A method for preparing a solid-state battery, characterized in that: include: Provide positive electrode sheets, solid electrolyte membranes and negative electrode sheets; Assembling the positive electrode plate, the solid electrolyte membrane and the negative electrode plate into a battery cell, and encapsulating the battery cell to obtain a solid-state battery; The method for preparing the positive electrode sheet and the solid electrolyte in the solid electrolyte membrane comprises: Providing sulfide electrolytes and single-ion conductor monomers; The sulfide electrolyte is mixed with the single ion conductor monomer, and the single ion conductor monomer is initiated to polymerize in situ on the surface of the sulfide electrolyte to form a coating layer, so as to obtain a solid electrolyte; the coating layer is a single ion conductor polymer; Wherein, the single ion conductor monomer is selected from at least one of the substances of structural formula (1), structural formula (2), structural formula (3), structural formula (4), structural formula (5) and structural formula (6); In the formula, R is selected from at least one of H, Cl, and CH3.

7. The preparation method according to claim 6, characterized in that: Provide sulfide electrolytes and single ion conductor monomers, including: Dispersing the sulfide electrolyte in a first solvent to obtain a first solution; wherein the first solvent is a solvent having a polarity index lower than 2.5; The initiator and the single ion conductor monomer are dispersed in a second solvent to obtain a second solution; wherein the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, ammonium persulfate, 2,4,6-trimethylbenzoyldiphenylphosphine, and benzophenone, and the second solvent is a solvent with a polarity index of 3 to 7.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the sulfide electrolyte to the first solvent is (15-45):

100.

9. The preparation method according to claim 7, characterized in that: The mass ratio of the single ion conductor monomer, the initiator and the second solvent is (0.3-3):(0.01-0.03):

100.

10. The preparation method according to any one of claims 7 to 9, characterized in that: The sulfide electrolyte is mixed with the single ion conductor monomer, and the single ion conductor monomer is initiated to polymerize in situ on the surface of the sulfide electrolyte to form a coating layer to obtain a solid electrolyte, comprising: mixing the first solution and the second solution to obtain a mixed solution; Initiating the in-situ polymerization of the single ion conductor monomers in the mixed solution on the surface of the sulfide electrolyte to form a coating layer; wherein the initiation method is light irradiation, heating or microwave radiation; The first solvent and the second solvent are removed from the mixed solution to obtain a solid electrolyte.

Citation Information

Patent Citations

  • Positive electrode lithium supplementing material with core-shell structure as well as preparation and application of material

    CN111682181A

  • Sulfide electrolyte membrane as well as preparation method and application thereof

    CN113782824A

  • Single lithium ion polymer electrolyte membrane and battery comprising same

    CN114335715A

  • Silicon-based composite negative electrode material, preparation method thereof and electrochemical energy storage device

    CN114400306A

  • Modified solid electrolyte, preparation method thereof and all-solid-state battery

    CN115863749A